2008
DOI: 10.1136/bjo.2008.138479
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of severe intraocular inflammation following intravitreal injection of bevacizumab (Avastin)

Abstract: Characteristic features of an inflammation induced by bevacizumab injection include an early onset with painless loss in VA mostly without conjunctival or ciliary injection. Patients respond to systemic or topical cortisone treatment with slow recovery but without permanent damage. Vitreous haemorrhage and infectious endophthalmitis might be differentiated by time course and symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
73
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(79 citation statements)
references
References 21 publications
2
73
1
3
Order By: Relevance
“…The clinical features of bevacizumab uveitis: gathered from previous studies and our patient-are as follows: [2][3][4][5][6][7] • Presentation on the first or second day after injection • Absence of pain Unlike in the reported series, our patient showed nongranulomatous inflammation that did not respond to intense topical steroid or intravitreal dexamethasone, necessitating vitrectomy. 2 He also showed a hypopyon that could be aspirated on anterior chamber tap. Our patient also underwent vitrectomy and the transient improvement was possibly due to the intravitreal dexamethasone administered along with the intravitreal antibiotics at the conclusion of surgery.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…The clinical features of bevacizumab uveitis: gathered from previous studies and our patient-are as follows: [2][3][4][5][6][7] • Presentation on the first or second day after injection • Absence of pain Unlike in the reported series, our patient showed nongranulomatous inflammation that did not respond to intense topical steroid or intravitreal dexamethasone, necessitating vitrectomy. 2 He also showed a hypopyon that could be aspirated on anterior chamber tap. Our patient also underwent vitrectomy and the transient improvement was possibly due to the intravitreal dexamethasone administered along with the intravitreal antibiotics at the conclusion of surgery.…”
Section: Discussionmentioning
confidence: 62%
“…This explains why some patients in a prior report needed steroid therapy for up to two months. 2 Studies having shown the presence of bevacizumab in the vitreous for up to three months and as in our patient, prolonged systemic steroid may be necessary. 8,9 Alternatively, systemic steroids can be substituted with long acting intravitreal or periocular steroids.…”
Section: Discussionmentioning
confidence: 99%
“…A larger protein load, a result of the additional Fc fragment, might also be a cause of clusters of sterile endophthalmitis reported in Canada [18] and worldwide [19]. Gower et al [12] also reported an 80% higher risk of endophthalmitis with Avastin compared to Lucentis (HR, 1.8%; 99% CI, 1.2-2.8).…”
Section: Potential Impact Of Differences In the Molecular Structurementioning
confidence: 83%
“…Mozayan and Farah [12] reported five cases of acute anterior uveitis presenting with severe pain and photophobia occurring within 2– 24 h after the injection. Georgopoulos et al [13] reported eight cases of uveitis presenting within 2 days after the injection with anterior uveitis, none with hypopyon and five with retinal infiltrates. The largest series to date was by Williams et al [14], who retrospectively reviewed 100,654 intravitreal injections between 2006 and 2013.…”
Section: Discussionmentioning
confidence: 99%